Basic geotechnical characteristic of soft clay stabilised with cockle shell ash and silica fume - Suwito, Anang Rustanto; Muzamir, Hasan; Muhammad Syamsul Imran, Zaini (Penerbit UMP, 2024)
Soft clay soils can present challenges such as expansion, high malleability, limited water flow, and reduced load-bearing capability especially in areas with periodic rainfall. Therefore, it is imperative to employ soil enhancement methods in order to alter the problematic characteristic of soft clay soil. Presently, the predominant technique for soil stabilisation is the utilisation of traditional stabilisers such as cement and lime which harm the environment. This investigation examines the geotechnical characteristic of clay soil that has been treated with waste materials which are cockle shell ash and silica fume for stabilisation purposes. The objective is to comprehend the impact of integrating cockle shell ash and silica fume on the geotechnical parameters of clay, with the aim of enhancing its suitability for construction applications. Several laboratory experiments were performed to assess adjustments in important characteristics such as Atterberg limits, specific gravity and compaction behaviour of soil sample. The result shows a significant decrease in liquid limit (13.8% depletion), reduced specific gravity (4.2% depletion), decreased maximum dry density (3.8% depletion) and higher optimum moisture content (2.9% enhancement). The presence of cockle shell ash and silica fume greatly modify the characteristic of soft clay soil, implying its potential as a viable and environmentally-friendly soil stabiliser.